Status and way-forward in breeding potato (Solanum tuberosum) for resistance to late blight - GOPAL, J (The Indian Journal of Agricultural Sciences, 2023)
Improving host resistance to late blight (Phytophthora infestans) has been a major concern of potato breeders since the Irish famine of 1840s. Since then, a number of late blight resistant potato (Solanum tuberosum L.) cultivars have been developed using both conventional and molecular techniques. However, resistance to late blight did not last long and broke down due to the emergence of more virulent races of Phytophthora infestans. This perspective paper presents the status of sources of resistance to late blight, defence mechanism of host against the pathogen and late blight resistance genes mapped, cloned, and transferred to cultivated potato. Considerable progress has been made in all aspects of breeding potato for resistance to late blight. However, a critical appraisal of the status of potato breeding for resistance to late blight suggests the continued need to identify new sources of resistance, transfer of resistance genes from diverse sources and stacking them in maximum number into individual plants. Other breeding strategies to combat this dreaded disease are also discussed.